Penentuan bidang unggulan akademik universitas melalui metode topik Linear Discriminant Analysis (LDA) - Mramra , Welianus Yohanes Yehuda; Nataliani, Yessica (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
The identification of academic flagship areas is crucial for higher education institutions as it helps enhance academic reputation and produce graduates who are competent in the workforce. However, the determination of these flagship areas is often subjective. Therefore, this study aims to identify the academic flagship areas at XYZ University using the Topic Modeling Latent Dirichlet Allocation (LDA) method. In this study, the LDA method is specifically used in the research field to analyze research journals at XYZ University from 2017 to 2021. The research results reveal three main topics that dominate the academic publications at XYZ University: business risk analysis, application system implementation particularly related to the pandemic, and information management with a framework in information technology. Based on this analysis, the flagship areas of XYZ University can be concluded to be in the fields of Information Technology and Business. Consequently, the University can more efficiently direct research resources and academic programs, as well as strengthen collaborations and its reputation as a center of excellence in these fields.